2006
DOI: 10.1111/j.1574-6968.1997.tb10482.x
|View full text |Cite
|
Sign up to set email alerts
|

Acridine orange as an indicator of bacterial susceptibility to gentamicin

Abstract: We have studied the response of Escherichia coli NCTC10418 to gentamicin with flow cytometry. The susceptibility of individual bacterial cells to the antibiotic was assessed by differential staining using the metachromatic dye, acridine orange. Exponential phase cultures were exposed to the minimum bactericidal concentration of gentamicin and analysed at regular intervals over 90 min. Within 60 min of exposure to the drug, two sub-populations of organisms could be distinguished in cultures by their different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The other dentin segment was washed with 100 L PBS and stained with 50 L 0.01% acridine orange; such dye has the ability to bind with bacterial RNA-emitting red fluorescence and to bind with bacterial DNA-emitting green fluorescence (20,21). This information allows analysis of the bacterial metabolism because cells in the log phase emit red fluorescence and those in the stationary phase emit a green fluorescence (11, 19 -22).…”
Section: The Determination Of Bacterial Viabilitymentioning
confidence: 99%
“…The other dentin segment was washed with 100 L PBS and stained with 50 L 0.01% acridine orange; such dye has the ability to bind with bacterial RNA-emitting red fluorescence and to bind with bacterial DNA-emitting green fluorescence (20,21). This information allows analysis of the bacterial metabolism because cells in the log phase emit red fluorescence and those in the stationary phase emit a green fluorescence (11, 19 -22).…”
Section: The Determination Of Bacterial Viabilitymentioning
confidence: 99%
“…The use of such processing software offers the feasibility of identifying as much as possible metabolic modifications, which are associated to cell shape modifications, allowing the evaluation of a density profile (metabolism) and cell morphology. In addition, the density profile derived from the Acridine Orange (AO) stained cells, also provides information on the metabolic activity (11,12). The dimension index was calculated by delineating the cells.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the Materials and Methods section, leukocytes were stained with less AO (0.25 μM) [9] than the 20 μM AO which Bruno and Mayo originally used on germinating Bacillus spores [1] or the 66.3 μM AO final concentration used in the present studies. The author explored AO concentrations as low as 13.25 μM, but noted only green vegetative Bacillus cells at the 13.25 μM concentration (data not shown) perhaps because AO could not penetrate the vegetative cells to reach mRNA at this lower concentration without the aid of a detergent to permeabilize the cells [4]. Figure 2 illustrates the repeated observation of increased fluorescence in the orange-red region (>590 nm) from day 0 to days 1 and 2 post-germination induction with 2 % dextrose or TSB.…”
Section: Methodsmentioning
confidence: 93%
“…Mason and Lloyd [4] have shown that orange-red AO fluorescence beyond 550 nm is correlated with metabolic activity and bacterial viability. In the present work, the author reinvestigates this phenomenon, documents its existence, and attempts to explain the fluorescence microscopy versus spectrofluorometry paradox in terms of spectral emission overlap and the metachromatic nature of AO.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation